PENGEMBANGAN ALAT DAN PROSEDUR UJI HYDRAULIC CONDUCTIVITY (KOEFISIEN PERMEABILITAS) TANAH HALAMAN I CANDI PRAMBANAN BESERTA PEMETAAN HASIL UJI DI LAPANGAN - , WILLIAM HENDRA PARULIAN SIAGIAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The post-rain puddles that happened in the Main Yard of Prambanan Temple is very bothering visitor mobility. Related technical data collecting of soil characteristic in the yard of Prambanan Temple require to be done to get correct solution of this problems. Coefficient permeability represent one of the very important parameter to be determined. Quick and simple field direct of permeability testing was needed to collect data which is represented the condition in field. Preparation in making device model and testing procedure conducted by developing field permeability testing devices which have been done by Forchheimer (1930), Sunjoto (1988), Putra and Setyanto (2012), and also Takeshita and Komatsu (2012). Testing procedure development was also based on constant-head and falling-head permeability testing methode and principle. Laboratory test like constant-head, done as the comparison with insitu test result. Hydraulic conductivity soil mapping use the Arcview GIS 3.3 software. Two models of permeability testing that was used, Model I (immediate flow model) and Model II (constant discharge model). Both of developed hydraulic conductivity device model and testing procedure at this research is effective enough, efficient, economic, simple, and easy to determine field permeability coefficient value of sandy soils. Soil permeability coefficient in unsaturated condition (kunsat) can be obtained by using Model II without making Soil Water Characteristic Curve that needs suction matrix measurement which costly enough. Presentation of soil permeability value in mapping that use Arcview GIS 3.3 software can explain the Prambanan Temple Yard soil permeability character and condition and also spatial relationship between one point with other point or between geospasial data. Keywords: puddle, device model, testing procedure, permeability coefficient